2021
DOI: 10.3390/ijerph18010340
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the SARS-CoV-2 Outbreak on the Psychological Flexibility and Behaviour of Cancelling Medical Appointments of Italian Patients with Pre-Existing Medical Condition: The “ImpACT-COVID-19 for Patients” Multi-Centre Observational Study

Abstract: Psychological distress imposed by the SARS-CoV-2 outbreak particularly affects patients with pre-existing medical conditions, and the progression of their diseases. Patients who fail to keep scheduled medical appointments experience a negative impact on care. The aim of this study is to investigate the psychosocial factors contributing to the cancellation of medical appointments during the pandemic by patients with pre-existing health conditions. Data were collected in eleven Italian hospitals during the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…Specifically, the fear of infection with COVID-19 accounted for one third of postponed or canceled appointments, which has also been observed in other medical sectors (48,49). This patient group may have tried to cope with the perceived risk due to pre-existing health conditions by a general avoidance behavior toward situations with potentially elevated infection risk-such as doctor's offices -, which has also been reported in other studies (50,51).…”
Section: Cad Patients' Use Of Health Care During the Covid-19 Pandemicsupporting
confidence: 61%
See 1 more Smart Citation
“…Specifically, the fear of infection with COVID-19 accounted for one third of postponed or canceled appointments, which has also been observed in other medical sectors (48,49). This patient group may have tried to cope with the perceived risk due to pre-existing health conditions by a general avoidance behavior toward situations with potentially elevated infection risk-such as doctor's offices -, which has also been reported in other studies (50,51).…”
Section: Cad Patients' Use Of Health Care During the Covid-19 Pandemicsupporting
confidence: 61%
“…We further found that a decrease in family visits and a lower frequency of leaving homes since the pandemic were associated with decreased GP consultations, worsening of CAD symptoms, more anxiety and depressive symptoms, as well as a higher individual risk perception. It might be possible that reduced family visits and/or staying at home increased loneliness ( 64 ), which has been found recently to be associated with an increased likelihood of canceling medical appointments ( 50 ). Further, mental health was more impaired in individuals who reduced their social contacts and who belonged officially to a COVID-19 risk group ( 62 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirmed the results of two recent online cross-sectional surveys ( 12 , 32 ) and highlighted that those difficulties in receiving MS-related healthcare services, psychological assistance, and rehabilitation therapy are related to negative psychological outcomes for PwMS, as it is reported for people with other chronic conditions. Interestingly, however, people with chronic diseases have been reported to exhibit a high likelihood of medical appointment cancellation during the pandemic and this behavior correlates with levels of COVID-19-related anxiety ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be attributed to the different therapeutic techniques performed in the physiological systems affected ( 3 , 5 ). The DASS-21 test showed an improvement in the mental health status of the population enrolled in this study, obtaining an increase of 26% related to the mild score for anxiety, 44% in the mild stress score, and 18% in the mild depression score; however, the use of a single technique or test in the psycho-emotional evaluation must be interpreted with caution due to the reliability in the answers given by the patients ( 16 ).…”
Section: Discussionmentioning
confidence: 81%